Factors influence perception of domestic tourist towards creative tourism of Labu Sayong in Kuala Kangsar / Auni Fathiah Abd Fatah, Nur Shazmeen Kamarudin and Rashidah Abdul Aziz - Abd Fatah, Auni Fathiah (2015)
Tourism is the important and largest industry in the world. Tourism is one of the economic sector and earning industry in Malaysia. Malaysia have target to capture a place within the top 10 countries in the world in terms of tourist arrival and preferred destination. Besides that, tourism is a dynamic and competitive industry that requires ability to adapt constantly to customer’s changing needs and desires the customer’s satisfaction, safety and enjoyment are particularly the focus of tourism businesses. The tourism industry offers many specialized forms of tourism in order to meet the increasingly diverse and the unique requests of a demanding public and one of that is Creative Tourism. Creative tourism refer to tourism which offers visitors the opportunity to develop their creative potential through active participation in courses and learning experiences, which are characteristic of the holiday destination where they are taken to. Creative tourism also can consider as a new generation of tourism by involving the tourists and local participation in the creation of the tourist products. Satisfaction of tourist is overall evaluation that is based on the total purchase consumption and experience. In general, satisfaction has been conceptualized in terms of whether the product or service meets consumer needs and expectation. In this research, the factors influence domestic tourist perception towards creative tourism such as activities, environments, awareness, motivation and people. The result of this study indicates there is positive relationship between factor influence tourist perception and satisfaction of the tourist. Last but not least, further research should be enhancing to improve the Creative Tourism in Malaysia.